Analysis of Factors Affecting Impulse Buying on Shopee and TikTok Live Shopping Platforms: A Conceptual Paper - Helda Widyarani Lutviari; Widodo, Arry; Silvianita, Anita; Rubiyanti, Nurafni (PT FORMOSA CENDEKIA GLOBAL, 2024)
The presence of live shopping on e-commerce platforms such as Shopee and TikTok has created a new trend called impulse buying, where customers make purchases spontaneously and without prior planning. Based on trend analysis, several factors have been identified as influences on impulse buying in live shopping, namely Fear of Missing Out (FOMO), Scarcity message, Shopping Lifestyle, Price Discount, and Perceived Enjoyment. This study aims to evaluate the impact of these variables on impulse buying behavior on the Shopee Live and TikTok Live live shopping platforms. The research sample will consist of consumers who have made impulse purchases while watching live shopping on both platforms. This research uses a quantitative approach with the Structural Equation Modeling (SEM) method and the Partial Least Square (PLS) approach using SmartPLS 3.0 software. It is hoped that this research can provide new insights in understanding the phenomenon of impulse buying on Shopee Live and TikTok Live live shopping, and provide recommendations for live shopping platforms to improve their marketing strategies to increase impulse buying